2019
DOI: 10.1016/j.celrep.2019.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Acute Iron Deprivation Reprograms Human Macrophage Metabolism and Reduces Inflammation In Vivo

Abstract: Summary Iron is an essential metal that fine-tunes the innate immune response by regulating macrophage function, but an integrative view of transcriptional and metabolic responses to iron perturbation in macrophages is lacking. Here, we induced acute iron chelation in primary human macrophages and measured their transcriptional and metabolic responses. Acute iron deprivation causes an anti-proliferative Warburg transcriptome, characterized by an ATF4-dependent signature. Iron-deprived human macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 83 publications
8
83
3
Order By: Relevance
“…Since the hepcidin-ferroportin axis evolved for the explicit purpose of iron-withholding and antimicrobial defense, it is therefore reasonable to anticipate that HFE variants result in blunted macrophage-mediated inflammatory responses. Published reports support the concept that low to moderate (vs. high) macrophage iron-loading has anti-inflammatory effects [57][58][59][60]. However, associations of sTFR levels and the sTFR-ferritin index with rapidity of onset of neuropathy in this study were not affected by adjusting for inflammation (hsCRP levels) in regression models, suggesting that iron availability may also impact susceptibility independent of inflammation or HFE genotype.…”
Section: Plos Onecontrasting
confidence: 65%
“…Since the hepcidin-ferroportin axis evolved for the explicit purpose of iron-withholding and antimicrobial defense, it is therefore reasonable to anticipate that HFE variants result in blunted macrophage-mediated inflammatory responses. Published reports support the concept that low to moderate (vs. high) macrophage iron-loading has anti-inflammatory effects [57][58][59][60]. However, associations of sTFR levels and the sTFR-ferritin index with rapidity of onset of neuropathy in this study were not affected by adjusting for inflammation (hsCRP levels) in regression models, suggesting that iron availability may also impact susceptibility independent of inflammation or HFE genotype.…”
Section: Plos Onecontrasting
confidence: 65%
“…In fact, a link between iron homeostasis and glycolysis in macrophages is documented, as acute iron depravation results in profound metabolic changes, particularly an increase in glucose metabolism. These changes are associated with anti-inflammatory properties in human macrophages (56). As it has been recently shown that macrophages carefully leverage their metabolism to fuel effector responses, it is tempting to speculate that in oxLDL stimulated cells, high Treml4 expression limits Slc40a1 expression, maintaining intracellular iron levels that facilitate controlled glycolytic flux.…”
Section: Discussionmentioning
confidence: 99%
“…71 Conversely, there was a decrease in genes involved in mitochondrial oxidation. 72 This is logical given that one of functions of the mitochondria is the formation of Fe-S clusters that acts as a co-factor F I G U R E 2 Electron microscopy of closely interacting adipocytes and macrophages: invaginated lipid structures budding off adipocytes and many vesicular structures resembling exosomes. Adipose tissue was collected from lean chow-fed C57BL/6J mice, cut into 1 mm pieces, and immediately fixed in 2.5% glutaraldehyde, before being prepared by Vanderbilt Imaging Core for TEM imaging.…”
Section: Lipid Bufferingmentioning
confidence: 99%